Mapping the annual cycle of temperature in Iceland - Halldor Bjornsson; Trausti Jonsson; Sigríđur Sif Gylfadottir; Einar Orn Olason (Meteorologische Zeitschrift, 2007)
We present maps of monthly average temperature for the period 1961-1990. To construct the maps we first calculated monthly temperature means for the period 1961-1990 at each available station in Iceland, and then we spatially interpolated the results. The spatial interpolation procedure consisted of two steps: de-trending and kriging. In the de-trending step an 8-component linear model was fitted to the temperature data, and the residual from the linear model calculated. In the kriging step, the residuals were spatially interpolated to a map of Iceland using kriging. The results from the linear model were added to the interpolated residual field to produce a map of mean temperature for the month. This method was employed for the 12 calendar months and for the annual mean. Following this we constructed similar maps for monthly averages of daily maximum and daily minimum temperatures. Using jack-knifing to estimate the accuracy of the maps yielded an error estimate of ±1°C.